The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.2172/5012308
|View full text |Cite
|
Sign up to set email alerts
|

Study of impurities in the Tandem Mirror Experiment using extreme-ultraviolet spectroscopy

Abstract: Impurities in the Tandem Mirror Experiment (TMX) have been studied using extreme ultraviolet spectroscopy. Three time-resolving absolutely-calibrated normal-incidence monochromators, one on each section of TMX, were used to study the impurity emissions in the wavelength range of 300 A -1600 A. The instruments on the east end cell and central cell were each capable of obtaining spatially-resolved profiles from 22 chords of the plasma simultaneously while the instrument on the west end cell monitored the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…In the central cell of TMX, the condition of the vacuum chamber walls was important in controlling impurity levels in the central-cell plasma [5,6]. Previous experiments showed that the brightnesses of carbon and oxygen emissions decreased as a result of titanium gettering.…”
Section: Sources Of Impurities Into the Central-cell Plasmamentioning
confidence: 99%
See 4 more Smart Citations
“…In the central cell of TMX, the condition of the vacuum chamber walls was important in controlling impurity levels in the central-cell plasma [5,6]. Previous experiments showed that the brightnesses of carbon and oxygen emissions decreased as a result of titanium gettering.…”
Section: Sources Of Impurities Into the Central-cell Plasmamentioning
confidence: 99%
“…(The ambient level of each oxygen ionization state was determined during an identical shot without injecting oxygen, and was substracted.) Most of the injected oxygen remains near the plasma edge, while only a small fraction penetrates inward; the penetration rate is approximately 3 cm-ms" 1 [6]. Examining a radial profile near the end of the shot (Fig.…”
Section: Sources Of Impurities Into the Central-cell Plasmamentioning
confidence: 99%
See 3 more Smart Citations